2020
DOI: 10.1037/tra0000881
|View full text |Cite
|
Sign up to set email alerts
|

Social and psychological consequences of the COVID-19 pandemic in African-American communities: Lessons from Michigan.

Abstract: The mental health consequences of the Covid-19 pandemic are particularly relevant in African American communities, as African-Americans have been disproportionately impacted by the disease, yet they are traditionally less engaged in mental health treatment compared to other racial groups. Using the state of Michigan as an example, we describe the social and psychological consequences of the pandemic on African-American communities in the United States, highlighting community members' concerns about contracting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 7 publications
1
67
1
Order By: Relevance
“… 22 Posited reasons for a racial disparity in mental ill-health include fear of contracting the virus, bereavement of social contacts and the disproportionate impact of social distancing measures on BAME communities. 23 Although the patient did not report any direct discrimination by healthcare workers during the admission, his ethnicity may have contributed to his presentation through the indirect risk factors previously described in the literature. 22 23 …”
Section: Discussionmentioning
confidence: 77%
“… 22 Posited reasons for a racial disparity in mental ill-health include fear of contracting the virus, bereavement of social contacts and the disproportionate impact of social distancing measures on BAME communities. 23 Although the patient did not report any direct discrimination by healthcare workers during the admission, his ethnicity may have contributed to his presentation through the indirect risk factors previously described in the literature. 22 23 …”
Section: Discussionmentioning
confidence: 77%
“…Task shifting to provide psychosocial and peer-based support will also be useful such as using lay volunteers trained to provide human connectedness to address physical distancing and resultant isolation-a strategy well-adopted in LMICs. These approaches will also be beneficial in HICs in that effective management of the mental health consequences of the pandemic in historically marginalized communities requires a multilevel, community-wide approach led by culturally sensitive mental health professionals (99).…”
Section: Upholding Global Rights Conventions and Further Recommendationsmentioning
confidence: 99%
“…Widespread loss, grief, and loneliness, layered with challenges to the stability of livelihoods and social networks, are just a few of the insults to mental health and wellbeing that persist amidst the COVID-19 pandemic and its resulting social and economic upheaval [2,8,[36][37][38][39][40]. This study found that COVID-19 has impacted multiple psychosocial pathways, including household emotional health, nancial security, and children's education.…”
Section: Community Empowerment and Social Supportsmentioning
confidence: 81%
“…In the United States (U.S.), refugees and non-refugee immigrants face many barriers to optimal health and well-being [1][2][3][4][5]. All such barriers should be considered in the context of the turbulent healthcare and economic climate resulting from the COVID -19 pandemic, which has exacerbated health and socioeconomic inequities affecting minority populations [6][7][8][9][10]. As the U.S. continues experiencing a rising death toll and widened gaps in socioeconomic and health parameters due to COVID-19, the adverse impact on vulnerable refugee and non-refugee immigrant populations must be recognized and mitigated [6,7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%